Keeping up with evidence-based recommendations: a qualitative interview study with general practitioners in Germany on information-seeking behaviour in cardiovascular care - Arnold, Christine; Hennrich, Patrick; Wensing, Michel; Ullrich, Charlotte (BMC primary care, 2023)
Due to the nature of their work, general practitioners (GPs) need to be up to date with evidence in various medical domains. While much synthesised research evidence is easily accessible nowadays, in practice, the time to search for and review this evidence proposes a challenge. In German primary care, the knowledge infrastructure is rather fragmented, leaving GPs with relatively few primary care specific resources of information and many resources from other medical fields. This study aimed to explore GPs information-seeking behaviour regarding evidence-based recommendations in cardiovascular care in Germany.
Veröffentlicht: 25. Mai 2023
Gesehen am 21.07.2023